Use of computer microtomography to assess the quality of endodontic tooth treatment using modern instruments (Эндодонтия Today, 2020)
With the help of micro-CT it was found that the preparation of the root canal by the Pro-Taper tool significantly extends the mouth and upper third of the canal, respectively by 56.1% and 41.7%, and by the SAF instrument by 51.5% and 50.8%. The area of the apical foramen widened by 26.3% when treated with Pro-Taper, which is significantly higher than with the SAF (7.9%).